1993
DOI: 10.2134/agronj1993.00021962008500040022x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Efficiency Component Analysis: An Evaluation of Cropping System Differences in Productivity

Abstract: The development of cropping systems that use N efficiently requires methods that evaluate system differences in N use. A procedure, based conceptually on soil and plant processes that affect N use, was developed to evaluate differences in N use efficiency among cropping systems. The method uses measurements of yield, grain N, aboveground plant N, applied N, and postharvest inorganic soil N to partition cropping system differences in yield and grain N into N efficiency components. The components consist of N su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(105 citation statements)
references
References 8 publications
(12 reference statements)
12
88
0
5
Order By: Relevance
“…This benefit decreased progressively with increases in the N fertiliser rate, to the point that, at 160 kg ha -1 of N, differences between CT and NT were negligible. These results, even though obtained in trials in which the NT technique was applied for one year only, highlighted the fact that the lower soil N availability as a result of the application of NT can play a crucial role in determining the differences in grain yield between the two tillage systems, in accordance with the report of Huggins and Pan (1993). On the other hand, soil cultivation (i.e.…”
Section: Resultssupporting
confidence: 84%
“…This benefit decreased progressively with increases in the N fertiliser rate, to the point that, at 160 kg ha -1 of N, differences between CT and NT were negligible. These results, even though obtained in trials in which the NT technique was applied for one year only, highlighted the fact that the lower soil N availability as a result of the application of NT can play a crucial role in determining the differences in grain yield between the two tillage systems, in accordance with the report of Huggins and Pan (1993). On the other hand, soil cultivation (i.e.…”
Section: Resultssupporting
confidence: 84%
“…Depending on the crop rotation and level of N fertility, NRI has been found in the range 0.37-0.73 with higher N fertility tending to reduce NRI (Yamoah et al 1998). The NRI is similar to the grain N accumulation efficiency index proposed by Huggins and Pan (1993) who reported values of 0.45-0.55 for spring wheat. They found that the index was lower under NT than under CT and not affected by N application.…”
Section: Efficiency Of N Utilizationsupporting
confidence: 83%
“…Nitrogen use efficiency decreased with N addition but was little affected by year or tillage. Previous studies with a wider range of N application rate have shown that NUE decreased with NT and increasing rates of N application, and the effect of year was variable (Huggins and Pan 1993;Sowers et al 1994;Lopez-Bellido and Lopez-Bellido 2001). Nitrogen recovery at maturity (as measured by NRI and RAN) was also influenced more by N rate than by year (and associated variability in moisture conditions).…”
Section: General Discussion and Conclusionmentioning
confidence: 83%
See 1 more Smart Citation
“…Various parameters are commonly used in agronomic research to evaluate the efficiency of the response of crops to applied N. Both from a physiological and agronomic point of view, N use efficiency (NUE) is the result of two main biological processes: N uptake efficiency (NUpE), which is the ability of a crop to produce yield per unit of N available in the soil, and N utilization efficiency (NUtE) which is the ability of a crop to produce yield per unit of N taken up [9][10][11][12][13][14]. In field studies, other parameters can be calculated based on differences in crop yield or total N uptake between fertilized plots and Agronomy 2017, 7, 66 2 of 15 unfertilized controls using the 'difference method' [12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%